A comparative study of the yellow dent and purple flint maize kernel components by Raman spectroscopy and chemometrics - Kabuk, Hayrunnisa Nur; Kaplan, Ekin Su; Halimoğlu, Gökhan; Fausto, Rui; ILDIZ, GÜLCE ÖĞRÜÇ (My University, 2019)
In this investigation the potential of micro-Raman spectroscopy, coupled to a simple, standard chemometric method (principal component analysis, PCA), as a fast, cheap, field method to investigate maize kernel components (endosperm, germ and peel) is demonstrated. Particular emphasis was given to the determination of the relative protein and amylose/amylopectin contents in maize endosperm of yellow dent and purple flint corn species, the two major maize varieties produced in Turkey. It is shown that the studied yellow dent corn type has a comparatively larger content of protein (3.4%) and a higher amylopectin/amylose ratio in the endosperm than the studied purple flint variety (a 11% decrease of amylopectin was found in going from the studied yellow dent to the purple flint corn), while the germs of the two species differ mostly by the presence of a slightly larger amount of starch in the case of the yellow dent corn, the oil composition of both species being identical within the resolution of the used method of analysis. The spectra of the maize peels reveal essentially the presence of cellulose and lignin in similar amounts in the two types of corn. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Yellow Dent; Purple Flint Maize Kernel; Raman Spectroscopy; PCA